Danby Pickering, ed., The Statutes at Large, from the Twelfth Year of Queen Anne, to the Fifth Year of King George I: To which Is Prefixed, a Table Containing the Titles of all the Statutes During that Period, Vol. XIII (Cambridge, UK: Joseph Bentham, 1764), 306-07. CAP. LIV—An Act for the more effectual securing the Peace of the Highlands in Scotland, Enacted November 1, 1716 (anno primo Georgii I) - (:unkn) unknown (General Publisher, 1716)
Prohibited any person within the Scottish Highlands from possession any broad sword, target, poynard, whingar, durk, side-pistol or side-pistols, or gun, or any other warlike weapons. Violators shall forfeit such arms and fined not less than five nor more than forty pounds sterling, and imprisoned until such fine is paid.
--
Keywords: POSSESSION